APULEIANA: TEXTUAL NOTES ON BOOK I OF THE METAMORPHOSES. (12th May 2014) - Kenney, E. J.
Abstract : Zimmerman's edition of this extraordinary novel (Oxford 2012) offers a well-constituted text based on consistently reliable editorial judgement, together with a substantial and informative preface and a full bibliography. But the last critical word has never been said, and a study of Book I has thrown up the following selection of passages which it is suggested may deserve further editorial attention.